2020
DOI: 10.1093/jac/dkaa104
|View full text |Cite
|
Sign up to set email alerts
|

Indications for the use of highest priority critically important antimicrobials in the veterinary sector

Abstract: Background Among the measures taken to preserve the clinical efficacy of highest priority critically important antimicrobials (HP-CIAs), the WHO has recommended avoiding their use in food-producing animals. Little is known regarding the indications for which different antimicrobial classes are used in animals, even in countries where data on antimicrobial use are available. Objectives To outline, in a narrative review, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 57 publications
1
37
0
1
Order By: Relevance
“…In addition, ammonia levels above 25 ppm reduced the colonization of beneficial bacteria such as Lactobacillus and increased the number of Moraxella and Streptococcus species in the nasal cavities of exposed pigs [26]. Antimicrobial exposure is another key environmental factor that can affect the development of URT microbiome at early stages of life, especially because antimicrobials are widely used for control of post-weaning diarrhoea [28]. Antimicrobial treatment perturbs the URT microbiome homeostasis regardless of the drug used (tylosin, ceftiofur, tulathromycin, oxytetracycline or penicillin) and the administration route (in-feed, parenteral or intramuscular) [29,30].…”
Section: Initial Colonization and Development Of The Respiratory Tracmentioning
confidence: 99%
“…In addition, ammonia levels above 25 ppm reduced the colonization of beneficial bacteria such as Lactobacillus and increased the number of Moraxella and Streptococcus species in the nasal cavities of exposed pigs [26]. Antimicrobial exposure is another key environmental factor that can affect the development of URT microbiome at early stages of life, especially because antimicrobials are widely used for control of post-weaning diarrhoea [28]. Antimicrobial treatment perturbs the URT microbiome homeostasis regardless of the drug used (tylosin, ceftiofur, tulathromycin, oxytetracycline or penicillin) and the administration route (in-feed, parenteral or intramuscular) [29,30].…”
Section: Initial Colonization and Development Of The Respiratory Tracmentioning
confidence: 99%
“…Many studies have demonstrated a close association between antibiotic use in food animal production and AMR in humans (Montoro-Dasi et al, 2020). Antimicrobial misuse in livestock is considered a threat to the clinical utility of antibiotics in both animals and humans (Vanderhaeghen & Dewulf, 2017); consequently, there has been a drive to avoid the use of highest priority clinically important antimicrobials (HP-CIAs) in food production animals to preserve their clinical efficacy (Lhermie et al, 2020). Unfortunately, in many disease conditions, adequate alternatives to HP-CIAs are lacking (Lhermie et al, 2020).…”
Section: Wgs Can Improve Surveillance Of Amr and Aid The Characterization Of Gene Transmission Dynamicsmentioning
confidence: 99%
“…Antimicrobial classes categorized as Veterinary Critically Important Antimicrobials can thus be the only available treatment option for specific severe infectious diseases in certain animal species [ 6 ]. Common indications for the use of CIAs of Highest Priority, for which sufficient treatment alternatives can be lacking in some instances, are enteric and respiratory infections in pigs, cattle and poultry, urogenital infections in cats and dogs and respiratory infections in horses [ 75 ]. However, even in such cases a potential for a reduction of antimicrobial use is seen by taking preventive measures, for instance vaccination and improvement of housing conditions.…”
Section: Discussionmentioning
confidence: 99%